Local Wisdom of the Banjar Society in a Collection of Stories of Satipis Apam Barabai By Ida Komalasari - Sri Normuliati; Nida Urahmah (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The presence of a collection of stories in Banjar language and set in South Kalimantan provides an overview to the reader about the local wisdom of the people in South Kalimantan. One of them is a collection of stories about Satipis Apam Barabai by Ida Komalasari. This study aims to reveal the local wisdom of the Banjar people in the collection of Satipis Apam Barabai stories by Ida Komalasari. This research is included in qualitative research with descriptive method. The data collected in the form of words, phrases, sentences, dialogues of the figures, and paragraphs related to the local wisdom of the Banjar people. After the data is collected, the data will be analyzed. The results of the study describe the local wisdom of the Banjar community which is tangible and intangible. Local wisdom that is tangible can be seen from the use of tapih bahalai as a tool to put babies to sleep. Intangible local wisdom is found in the advice that is trusted by the community, including messages not to lie down when it is sunset, messages to read Surah Al-Waqiah after sunset prayers, and it is forbidden to talk about other people while in the cemetery. Keywords: local wisdom, Banjar society, collection of stories Abstrak Kehadiran kumpulan kisah berbahasa Banjar dan berlatarkan tempat di Kalimantan Selatan memberikan gambaran kepada pembaca tentang kearifan lokal masyarakat di Kalimantan Selatan. Salah satunya adalah kumpulan cerita Satipis Apam Barabai Karya Ida Komalasari. Penelitian ini bertujuan untuk mengungkapkan kearifan lokal masyarakat Banjar dalam kumpulan cerita Satipis Apam Barabai Karya Ida Komalasari. Penelitian ini termasuk ke dalam penelitian kualitatif dengan metode deskriptif. Data-data yang dikumpulkan berupa kata-kata, frasa, kalimat, dialog para tokoh dan paragraf yang berhubungan dengan kearifan lokal masyarakat Banjar. Setelah data terkumpul, data dianalisis. Hasil penelitian mendeskripsikan tentang kearifan lokal masyarakat Banjar yang berwujud nyata dan yang tidak berwujud. Kearifan lokal yang berwujud nyata terlihat dari penggunaan tapih bahalai sebagai salah satu alat untuk menidurkan bayi. Kearifan lokal yang tidak berwujud terdapat pada petuah yang dipercayai oleh masyarakat, di antaranya pesan untuk tidak rebahan ketika menjelang magrib, pesan untuk membaca surah Al-Waqiah setelah salat magrib, dan dilarang membicarakan orang lain saat berada di kuburan. Kata kunci: kearifan lokal, masyarakat Banjar, kumpulan kisah